PENGARUH CITRA MEREK TERHADAP MINAT BELI PRODUK PEMBALUT WANITA MEREK SOFTEX (STUDI KASUS PADA KALANGAN MAHASISWI JURUSAN MANAJEMEN UNIVERSITAS NEGERI GORONTALO) - Sri Indriyani Lahay; Tineke Wolok; Djoko Lesmana Radji (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
The research aimed to find out to what extent the Influence of Brand Image towards Purchase Decision of Softex at Female Students at Department of Management, State University of Gorontalo. The research data were primary data gained by distributing a questionnaire to Female Students at Department of Management, State University of Gorontalo. The data analysis used simple linear regression through assistance of the SPSS Program. The research finding through t-test obtained significant value of T value (0,000) < alpha (0.05) and test value of T count (12,080) > T table (1,9893). The result was supported by the value of the regression coefficient value of 0,800 or higher than the scale of 0,05, so that it declared that Brand Image had a significant influence towards Purchase Decision of Softex at Female Students at Department of Management, State University of Gorontalo. In addition, based on the calculation of the determination coefficient, it obtained value (R²) for 0,640, which indicates that 64% of independent variable (Brand Image) had a contribution to influence Purchase Decision of Softex at Female Students at Department of Management, State University of Gorontalo. Meanwhile, the rest 0,36 or 36% was influenced by other variable such as product quality, price promotion, and others that were not explained and studied in the research. Based on the research finding, it can be concluded that the result of regression test shows that the variable of Brand Image had significant influence towards Purchase Decision of Softex by referring to result of regression coefficient where T count is higher than T table and the amount of contribution for Brand Image variable in influencing Purchase Decision variable.